An outstanding scientist, psychologist Viktor P. Sheinov celebrates his 80th anniversary! - Victor V. Znakov; Ludmila G. Pochebut; Georgij V. Losik (Peoples' Friendship University of Russia (RUDN University), 2020)
The article is dedicated to the anniversary of Viktor P. Sheinov, a prominent modern psychologist, active author and member of the editorial board of the RUDN Journal of Psychology and Pedagogics. Viktor P. Sheinov is rightfully considered a man of the world: his works are very popular among scientists and practical psychologists in Russia, Ukraine, Belarus, Armenia, Latvia, and many other countries. It is impossible to overestimate his contribution to the development of such areas of modern science as personality psychology, general, social, pedagogical and cross-cultural psychology, conflict resolution studies, psychodiagnostics, and psychometrics. Viktor P. Sheinov is the author of over 350 scientific and practical works, including 21 monographs (6 of which are translated into English and published abroad), as well as 40 books on practical psychology.